Highly efficient sulfimidation of 1,3-dithianes by Cu(I) complexes - Giribabu, Lingamallu; Singh, Surya P.; Patil, Nandkumar M.; Kantam, M. Lakshmi; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synthetic Communications, 2008)
A series of four Cu(I) complexes were tested for sulfimidation of 1,3-dithianes in the presence of [N-(p-tolysulfonyl)imino]phenyliodinane (PhI = NTs) as the nitrene-transfer agent. Cu(TMPhen)(PPh3)Br is an efficient catalyst with more than 90% yield of the corresponding product with less reaction time as compared to the literature copper(I) complexes.
Keywords: 1; 3-dithianes; Cu(I) complexes; PhI = NTs; sulfimidation

Electronically and catalytically functional carbon cloth as a permeable and flexible counter electrode for dye sensitized solar cell - Tathavadekar, Mukta; Biswal, Mandakini; Agarkar, Shruti A.; Giribabu, Lingamallu; Ogale, Satishchandra (Electrochimica Acta, 2014)
In this work we demonstrate that a conducting carbon cloth obtained by one-step pyrolysis of easily available cellulose fabric competes favorably with the commonly employed expensive platinum/FTO system as a counter electrode for dye sensitized solar cell (DSSC). In view of the low carbonization temperature (1000 degrees C) which forbids full graphitization, the nature of carbon in this case is represented by topologically randomly assembled nanoscale graphene units (turbostratic carbon). This morphology has high density of edge states and oxygen containing surface groups rendering multitude of catalytic sites for the reduction of I-3(-). Moreover the cloth is permeable to the dye and/or liquid electrolyte and its absorption properties also help retain the electrolyte. A fairly high efficiency of 5.8% is achieved using such cloth as a counter electrode as against 7% with the conventional Pt/FTO system. Moreover, the permeable property of the cloth eliminates a complete step of drilling hard TCO substrates for final dispensing of electrolyte into the device and the sealing process is also facile. In fact even the dye can be dispensed through the cloth. Finally, the flexibility of the carbon cloth can adapt easily to flexible/wearable DSSC designs. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: conducting carbon cloth; counter electrode; DSSC; without drilling

Substituent‐induced deformed ni–porphyrin as an electrocatalyst for the electrochemical conversion of water into dioxygen - Krishna, J. V. S.; Krishna, Narra Vamsi; Singh, Santosh K.; Shaw, Pankaj K.; Dhavale, Vishal M.; Vardhaman, Anil Kumar; Giribabu, Lingamallu (European Journal of Inorganic Chemistry, 2018)
The electrochemical water oxidation ability of complexes 5,15‐diphenylporphinatonickel(II) (A) and 5,15‐bis(3,5‐di‐tert‐butylphenyl)porphinatonickel(II) (B) in the oxygen evolution reaction (OER) have been investigated in an alkaline medium. Complex B was found to be kinetically and thermodynamically more active than complex A. The overpotential and Tafel slope of complex B are lower than those of complex A by 30 mV and around 45 mV/decade, respectively, which supports the higher activity of B. Moreover, stability tests endorse the sustainability of both samples under alkaline conditions. It has been found that the 3,5‐di‐tert‐butylphenyl substituent in B plays a decisive role in achieving a better OER onset potential and current than that obtained with A, which is a result of the modulation of the structural parameters of B. Furthermore, the measured OER activities of A and B have been correlated with their molecular arrangement as well as differences in their bonding characteristics and dipole moments. For further insight, the obtained results have been confirmed by a theoretical study.